Effect of ultrasonication duration and temperature on the stability and viscosity of MXene/water nanofluid - Abd Malek, Norhazwani; Ab Razak, Nur Najihah; Masuri, Siti Ujila; Saidur, Rahman; Tan, Kimhan; Jaafar, Che Nor Aiza; Supeni, Eris Elianddy (Malaysian Institute of Chemistry, 2024)
Despite some encouraging results that nanofluids offer to the scientific community, several challenges remain before their widespread adoption in industry. One significant challenge is the stability of nanofluids, which can lead to nanoparticle aggregation and affect viscosity. Ultrasonication is a common method used to disperse nanoparticles in base fluids. Therefore, the main aim of this work is to investigate the effect of ultrasonication duration and temperature on the stability and viscosity of MXenes (Ti3C2Tx)/water nanofluids. A nanofluid containing 0.05 wt% MXenes (Ti3C2Tx)/water was formulated by adopting three different ultrasonication durations, namely 60, 90 and 120 minutes. The Zeta potential value was used as an indicator of their stability. In conjunction with visual inspections, the stability of the samples was examined on Day 1, 7 and 30 after the nanofluids’ formulation. On Day 1, optimal stability was observed in nanofluids ultrasonicated for 90 minutes at the respective temperature, with moderate Zeta potential values exceeding -30 mV. However, stability decreased over time across all cases. Extending the ultrasonication duration to 120 minutes resulted in higher nanofluid’s viscosity. The temperature variations from 20 to 60°C did not show similar trend of the stability for some cases, potentially indicating particle agglomeration with changing temperatures. Hence, more investigations were suggested to get more information of the nanofluids, such as characterization techniques using microscopy. The stability could also be improved via other methods, such as integrating surfactants, varying pH level and nanoparticles concentration, and modifying nanoparticle surfaces and base fluid.